Representaciones sociales en torno al arte de la sastrería - Chasi Caisaguano, Julio César (2016)
This research seeks to analyze the devalued labor of a tailor, based on social representations existing in society. To do this, it was taken into account Ferdinand de Saussure’s fundamental ideology who is the father of semiology, Wilhelm Wundt, author of social behaviors and human actions, Perrie Bourdieu, author of the theory of lifestyle. Also, it was considered as reference the consumer profile of Ana Lucia Jaramillo Toro, among others scholars and issues that contributed to the project. The methodology used is qualitative – quantitative, interviews to experts in the area were conducted: Social Communication, History of Latacunga, Fashion design and tailoring, In addition, a survey was applied to a population of Latacunga in order to identify the level and type of clothing they use. In conclusion, the social representations issued by the mass media such as television, establish stereotypes in people changing the way they dress; and this is the main reason of the decline of sales and devalued labor of tailoring. It is also evidenced the loss of cultural traits as a result of this change.